A Practical Study to Develop the Performance of a Water Cooler by Using ‎Surplus Water to Reduce Electricity Power Consumption (Journal of University of Babylon for Engineering Sciences, 2022)
A 45-liter two-tap water cooler with a half-ton hermitic compressor and refrigerant R-22 was developed by taking a benefit of cold water in excess of the consumer’s need (Surplus water) and spraying it on the condenser of the refrigeration cycle of the device, with special design of a water drain pipe and a perforated basin fixed above the condenser and a bottom one that is fixed under the condenser to collect excess water. This design was implemented to reject condensing heat with a shorter time and drawing less electric current then lower electrical energy consumption compared to without using of surplus water. The study shows, the temperature of water decrease from (28℃) to the required degree of (4℃) after 70 minutes, while it reaches this degree after 52 minutes when using the cold surplus water under the same conditions. The results of the experiments show a large decreasing in the electricity energy consumption when using surplus water by 31% and this percentage reaches to 37% in severe running conditions, then this reduction in the electricity energy consumption can be used to provide more energy and reduce the problem of global warming. In addition, it decrease the time to cool water by 32% in severe running conditions and thus increasing the number of consumers of cold water, especially when water coolers were placed in crowded areas such as schools, colleges, and others in the summer season.